Determinant factors of anemia prevention behavior among female adolescents in border area: a path analysis on the health belief model - Nahak, Maria Paula Marla; Berek, Pius Almindu Leki (Intelektual Pustaka Media Utama, 2025)
Combating anemia in female adolescents may prevent long term effects of low birth weight, malnutrition, and growth failure (stunting) in their progeny. This study aimed to path-analyze the determinants of anemia prevention behavior in female adolescents with health belief model approach. This was an observational analytical study, conducted at SMAN 3 Atambua, East Nusa Tenggara, Indonesia, from May 7, 2024 to August 2, 2024. A total of 103 participants were selected by total sampling. The data collected by a set of questionnaires. This study revealed a direct and positive correlation between perceived threat (b = 2.43; 95% CI = 0.67 to 4.18; p = 0.007), perceived benefits (b = 1.99; 95% CI = 0.20 to 3.78; p = 0.029), perceived barrier (b = 2.74; 95% CI = 0.34 to 5.14; p = 0.025), self-efficacy (b = 1.76; 95% CI = 0.06 to 3.46; p = 0.042), cues to action (b = 1.96; 95% CI = 0.27 to 3.65; p = 0.022) and anemia prevention behavior. Knowledge is indirectly correlated to anemia prevention behavior through self-efficacy (b =2.25; 95% CI = 0.95 to 3.54; p = 0.001); perceived susceptibility is indirectly correlated to anemia prevention behavior through perceived threat (b = 2.01; 95% CI = 0.78 to 3.24; p = 0.001); perceived severity is indirectly correlated to anemia prevention behavior through perceived threat (b = 0.91; 95% CI = 0.01 to 1.81; p = 0.045). The implications of this study suggest that multifaceted interventions should be put in place that combine education, empowerment, overcoming barriers, and increasing the perceived threat and severity of anemia, all of which can improve anemia prevention behavior among female adolescents.